Effective Ocular Delivery of Eplerenone Using Nanoengineered Lipid Carriers in Rabbit Model - Abdelhakeem E (Dove Medical Press, 2021)
Eman Abdelhakeem, Mohamed El-nabarawi, Rehab Shamma Department of Pharmaceutics and Industrial Pharmacy, Faculty of Pharmacy, Cairo University, Cairo, EgyptCorrespondence: Rehab ShammaDepartment of Pharmaceutics and Industrial Pharmacy, Faculty of Pharmacy, Cairo University, Cairo, EgyptTel +20-0111-930-1245Email rehab.shamma@pharma.cu.edu.egBackground: Eplerenone (Epl) is a selective mineralocorticoid-receptor antagonist used for chronic central serous chorioretinopathy treatment. Our goal was to enhance the corneal performance of Epl-loaded nanostructured lipid carriers (NLCs) through surface modification using different coating polymers.Methods: Epl-loaded modified NLCs (Epl-loaded MNLCs) were prepared by coating the surface of Epl-loaded NLCs using different polymers, namely hyaluronic acid, chitosan oligosaccharide lactate, and hydrogenated collagen. A 3 1× 4 1 full factorial design was used to evaluate the effect of the surface modification on the properties of the prepared systems. Selected optimal Epl-loaded MNLCs were further evaluated for in vitro drug release, morphology, pH, rheological properties, corneal mucoadhesion, irritation, and penetration.Results: Epl-loaded MNLCs were successfully prepared with high drug-entrapment efficiency and nanosized particles with low size distribution. Transmission electron microscopy revealed nanosized spherical particles surrounded by a coating layer of the surface modifier. The pH, refractive index, and viscosity results of the Epl-loaded MNLCs confirmed the ocular compatibility of the systems with no blurring of vision. The safety and ocular tolerance of the optimal MNLCs were confirmed using the hen’s egg test on chorioallantoic membrane and by histopathological evaluation of rabbit eyes treated with the optimal systems. Confocal laser-scanning microscopy of corneal surfaces confirmed successful transcorneal permeation of the Epl-loaded MNLCs compared to the unmodified Epl-loaded NLCs, revealed by higher corneal fluorescence intensity at all time intervals.Conclusion: Overall, the results confirmed the potential of Epl-loaded MNLCs as a direct approach for Epl ocular delivery.Keywords: eplerenone, modified nanostructured lipid carriers, chronic central serous chorioretinopathy, surface modifiers